KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS X SMK NEGERI 2 LUBUK BASUNG - Khotimah, Sari Husnul; Tamsin, Andria Catri; Rasyid, Yulianti (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTThis article was written to describe the correlation of reading comprehension skill with the skill of writing the text of the result of observation of the tenth grade students of SMK Negeri 2 Lubuk Basung. This research is a quantitative research with descriptive method. The sample in this study amounted to 40 people. The data of this research is the result score skill test reading comprehension and the result score skill test of writing the text of the result of observation. Based on data analysis and discussion, the following three things are obtained. First, the skill of reading comprehension of the tenth grade students of SMK Negeri 2 Lubuk Basung is in very good qualificationÂ  (88,42). Second, the skill of writting the text of the result of observation of the tenth grade students of SMK Negeri 2 Lubuk Basung is in good qualification (82,50). Third, there is correlation of reading comprehension skill with the skill of writing the text of the result of observation of the tenth grade students of SMK Negeri 2 Lubuk Basung because tcount>ttable(2,13>1,68).Â Kata kunci: korelasi, membaca pemahaman, menulis, teks laporan hasil observasiÂ